The Level of Critical Thinking Ability of Upper Grade Students at SD Ngadirejo 1 in Physical Education in 2023 - Mochamad Jupri Azhari; Dhedhy Yuliawan; Ruruh Andayani Bekti (CV. Nusantara Sporta, 2023)
The research conducted at SDN Ngadirejo 1 was based on the results of observations that found that students' attitudes tended to be more passive in attending Physical Education lessons. Their behavior shows a lack of response to Physical Education learning. So the researcher took the formulation of the problem, namely how the level of critical thinking skills of the upper class students of SDN Ngadirejo 1, Kediri City, East Java. The aim of this study was to determine the level of critical thinking skills of the upper graders of SDN Ngadirejo 1. The research technique used a survey method with a questionnaire designed to determine the critical thinking abilities of upper graders of SDN Ngadirejo 1 in physical education. The research subjects taken were the upper class students of SDN Ngadirejo 1 with a total of 156 students with the sampling technique using total sampling. The results of this study indicate that the level of critical thinking skills of the upper graders of SDN Ngadirejo 1 is in the good category with a percentage analysis, the results of which show 77% with a frequency of 120 students. From the results of this analysis, it can be concluded that the upper graders of SDN Ngadirejo 1 have good critical thinking skills